Penguatan Kesadaran Sosial Islam dalam Ruang Digital Masyarakat Muslim Berbasis Pendekatan Historis - Refileli, Refileli; Supandri, Human Maufu (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
The development of digital technology has created new social spaces for Muslim communities to build and express Islamic social awareness. Digital spaces function not only as media of communication but also as arenas for the formation of solidarity and religious identity. This community service activity (Pengabdian kepada Masyarakat/PKM), based on a historical approach, was conducted in 2025 in Sukarami Sub-district, Selebar District, Bengkulu City, targeting Muslim communities, youth, and community-based Islamic media managers, in collaboration with religious leaders and local community institutions. This activity aims to strengthen Muslim communities’ understanding of the historical roots of Islamic social awareness and its positive actualization in the digital sphere. The methods employed included historical socialization, participatory discussions, and Islamic digital literacy training. The results indicate an increased awareness that digital space represents a continuation of Islamic social traditions as well as a new arena for shaping more open, inclusive, and transboundary social awareness.